Scaling properties of the regular dynamics for a dissipative bouncing ball model - Leonel, Edson D.; Oliveira, Diego F. M.; de Carvalho, R. Egydio (Elsevier B.V., 2007)
Some scaling properties of the regular dynamics for a dissipative version of the one-dimensional Fermi accelerator model are studied. The dynamics of the model is given in terms of a two-dimensional nonlinear area contracting map. Our results show that the velocities of saddle fixed points (saddle velocities) can be described using scaling arguments for different values of the control parameter. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Fermi accelerator; scaling laws; saddle velocities